PEREMPUAN DALAM TEKNOLOGI DIGITAL MARKETING BRAND - Hidayat, Andi Nurul (Pusat Studi Gender dan Anak, IAIN Palu, 2018)
Indonesian women in the ministries, companies, organizations, social institutions, entrepreneurs, activists, and show that women have an important role in Indonesia one of them is the positive impact of today's women in using technology increasingly significant growth and development increases with from the time of several months and years of childbirth innovation and ease the community it is also in feel by women or women that the trend of smartphones technology up to the current netbook can be used in terms of business side as well as with the Ads traditionally depicting men andwomen in a role that is quite stereotypical in terms of Marketing is neutral gender is not a trend but a shift in society. New approaches to gender fall into one of three categories that is used is a femvertising resurrection, a champion of feminine power and empowering women. In digital marketing brand technology.